(untitled) (mathematica didactica, 2026)
When students are asked to work on mathematical tasks, a change of representation e. g. can help them to perceive new solution processes. This article looks at possible processes involved in changing representation, based on situations in which a change of representation does not initially appear to work as expected. The abduction schema is used to investigate how learners can transfer their developed ideas to alternative representations, either with or without changes. The focus is on examining the processes of re-interpretation and new-interpretation in order to describe various procedures involved in changing representations.